Sustainability Accounting, Company Performance, On Company Value In Companies With Common Effect Model In IDX 30 Companies On The IDX - Dina Indah Permatasari; Sri Hartati Sidauruk (Jurnal Ekonomi, 2024)
This study aims to test and analyze the effect of Sustainability Accounting, financial performance on company value, on IDX 30 Companies Listed on the Stock Exchange. The population of this study is IDX 30 companies listed on the Indonesia Stock Exchange for the period 2021-2023, the sample selection in this study uses the purposive sampling method, namely the selection of samples based on predetermined criteria, so the number of samples successfully obtained is 7 IDX 30 companies. This type of research is quantitative research. The analysis method of this study uses multiple linear regression analysis, using Eviews13. The results of this study indicate that partially shows that economic sustainability accounting, social sustainability accounting have a significant effect on company value while environmental sustainability accounting, and company performance do not have a significant effect on company value. Based on the results of simultaneous analysis of independent variables, economic sustainability accounting, environmental sustainability accounting, social sustainability accounting and company performance have a significant effect on company value.